Understanding the Typology of Health Sector Corruption in Indonesia - Juwita, Ratna (UI Scholars Hub, 2023)
Health sector corruption is considered as one of the most serious barriers to the realisation of the right to health due to the complexity of the health care system structure. This research aims firstly to explain the international legal obligations of Indonesia concerning the right to health and anticorruption and subsequently explain the measures taken by Indonesia to realise its international legal obligations. Secondly, legally binding judgments on health sector corruption will be collected to formulate the typology of health sector corruption in Indonesia. The construction of the typology of health sector corruption is to pinpoint the pattern of corruption in the health sector. Thirdly, the typology will be utilised to assess whether anti-corruption measures in the health sector are fit to combat such health sector corruption. Based on the judgments collection studies, the typology of health sector corruption in Indonesia is divided into three types. These are grand corruption in the procurement process, obstruction of the justice process by cooperation between the corruptors and law enforcement agencies, and corruption related to decentralisation. By understanding the typology of health sector corruption, a number of targeted measures to strengthen the current anticorruption measures are proposed. These measures are: strengthen the mandatory e-procurement system, combat impunity by increasing anti-corruption awareness and discipline for the law enforcement agencies, and address the personal reasons why corruptors commit corruption by conducting targeted studies of this issue and apply a human rights approach to the current anticorruption measures.